2013
DOI: 10.3389/fnmol.2013.00020
|View full text |Cite
|
Sign up to set email alerts
|

L-type CaV1.2 deletion in the cochlea but not in the brainstem reduces noise vulnerability: implication for CaV1.2-mediated control of cochlear BDNF expression

Abstract: Voltage-gated L-type Ca2+ channels (L-VGCCs) like CaV1.2 are assumed to play a crucial role for controlling release of trophic peptides including brain-derived neurotrophic factor (BDNF). In the inner ear of the adult mouse, besides the well-described L-VGCC CaV1.3, CaV1.2 is also expressed. Due to lethality of constitutive CaV1.2 knock-out mice, the function of this ion channel as well as its putative relationship to BDNF in the auditory system is entirely elusive. We recently described that BDNF plays a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Amplitude of ABR wave I may reflect changes of synaptic potentials between inner hair cells and nerve fibers of spiral ganglion cells [13]. In this study, wave I peak amplitude was found to reduce immediately after 2 h of exposure to the 110 dB SPL sound stimulation, (p < 0.05, click, Figure 2A), corresponding to the elevations of hearing threshold.…”
Section: Reduction and Recovery Of Wave I Peak Amplitudesupporting
confidence: 48%
“…Amplitude of ABR wave I may reflect changes of synaptic potentials between inner hair cells and nerve fibers of spiral ganglion cells [13]. In this study, wave I peak amplitude was found to reduce immediately after 2 h of exposure to the 110 dB SPL sound stimulation, (p < 0.05, click, Figure 2A), corresponding to the elevations of hearing threshold.…”
Section: Reduction and Recovery Of Wave I Peak Amplitudesupporting
confidence: 48%
“…This allowed for hearing thresholds to be determined from both ears simultaneously, with each ear considered a separate data point. The results section shows the data with each ear counting as an individual biological replicate because both ears were exposed to noise and thresholds were obtained from the two ears separately, as previously described [ 33 , 34 ]. In addition, the supplementary data reports the hearing threshold results where the thresholds from both ears of each mouse are averaged and each mouse is counted as an individual biological sample.…”
Section: Methodsmentioning
confidence: 99%
“…The ethological results showed that Fgf13 cKO mice displayed impaired auditory function ( Figures 3A–C ) and gene deletion affected the wave I component but not the wave II-V in the click-evoked ABR test ( Figures 3D–F ). These results suggest that Fgf13 deletion selectively causes damage to SGN but not to the central auditory pathway, since the amplitude and peak latency of wave I reflect the function of the peripheral SGNs, whereas waves II-V indicate a function of the ascending auditory pathway ( Zuccotti et al, 2013 ; Eggermont, 2019 ). This observation was further supported by two results, abundant expression of FGF13 in SGNs of the inner ear ( Figure 1 ) as well as that the cKO mice functioned normally in the DPOAE test ( Figure 3G ), indicating an intact function for outer HCs.…”
Section: Discussionmentioning
confidence: 88%